2016
DOI: 10.1038/emm.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of the brain in the homeostatic regulation of energy and glucose metabolism

Abstract: Accumulated evidence from genetic animal models suggests that the brain, particularly the hypothalamus, has a key role in the homeostatic regulation of energy and glucose metabolism. The brain integrates multiple metabolic inputs from the periphery through nutrients, gut-derived satiety signals and adiposity-related hormones. The brain modulates various aspects of metabolism, such as food intake, energy expenditure, insulin secretion, hepatic glucose production and glucose/fatty acid metabolism in adipose tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
228
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(235 citation statements)
references
References 176 publications
(188 reference statements)
6
228
0
1
Order By: Relevance
“…Nutrient sensing mechanisms in mammals are also implicated in the regulation of energy homeostasis through processes other than food intake (Levin, 2006; Blouet and Schwartz, 2010; Morton et al, 2014), such as hormone secretion and energy expenditure (Morgan et al, 2004; Pocai et al, 2005; Le Foll et al, 2009; Roh et al, 2016). The homeostatic control carried out by nutrient sensing systems occurs at both central and peripheral levels.…”
Section: Impact Of Nutrient Sensing On Energy Homeostasismentioning
confidence: 99%
“…Nutrient sensing mechanisms in mammals are also implicated in the regulation of energy homeostasis through processes other than food intake (Levin, 2006; Blouet and Schwartz, 2010; Morton et al, 2014), such as hormone secretion and energy expenditure (Morgan et al, 2004; Pocai et al, 2005; Le Foll et al, 2009; Roh et al, 2016). The homeostatic control carried out by nutrient sensing systems occurs at both central and peripheral levels.…”
Section: Impact Of Nutrient Sensing On Energy Homeostasismentioning
confidence: 99%
“…Three major hypothalamic nuclei, such as ARC, VMN and PVN, actively participate in the regulation of glucose homeostasis [65]. In 1854, French physiologist Claude Bernard showed that brain lesion in dogs causes hyperglycemia and irst proposed that the CNS could be involved in the control of energy and glucose homeostasis.…”
Section: Hypothalamic Regulation Of Glucose Homeostasismentioning
confidence: 99%
“…Some neurons are excited by increased glucose level with more iring frequency while others are inhibited with less iring by same stimuli. The glucose sensitive neurons are located in the VMN, ARC, PVN, as well as the dorsal vagal complex in the brain stem [65]. Central glucose sensing also impacts systemic glucose metabolism.…”
Section: Glucose Sensingmentioning
confidence: 99%
“…Since the classical study by Claude Bernard, which showed that an injury to the floor of the fourth cerebral ventricle caused hyperglycemia, the involvement of the nervous system in the regulation of pancreatic endocrine function and metabolic control has been shown in many studies [17][18][19]. At the same time, the precise innervation patterns of islets were unknown, particularly in humans [9].…”
Section: Introductionmentioning
confidence: 99%